Plankton Biodiversity at Jabung Swamp, Lamongan and Tuban Districts (Biodiversitas Journal of Biological Diversity, 2016)
Plankton, an aquatic biota, often used as an indicator of water quality. The objectives of the research were to know: (1) diversity of both phyto- and zooplankton at Jabung swamp, East Java; (2) water quality at the swamp, and (3) diversity of fish that act as primary consumer of the plankton. Field sampling procedures were done at the swamp, followed with identification and data analysis at laboratory. Sampling locations were at the inlet, pools in the swamp and at the outlet. Sample were taken triplicate at each location between September and November, 1999 using a plankton net, while fish data were collected by interview and direct observation at the field. Thirty-one species of plankton were found in this research consisting of 17 species of phytoplankton and 14 species of zooplankton. The results of the plankton analysis indicate that Jabung swamp categorizes as moderately polluted at the inlet, polluted free at the pools inside the swamp, and lightly polluted at the outlet. There were 15 fish species found at the swamp both of cultivated and non-cultivated fish.Â© 2000 Jurusan Biologi FMIPA UNS SurakartaKey words: biodiversity, plankton, Jabung swamp, water pollution